Effect of whole body vibration therapy in the rat model of steroid-induced osteonecrosis of the femoral head - Tian, Jia-Qing; Wei, Teng-Fei; Wei, Yu-Rou; Xiao, Fang-Jun; He, Xian-Shun; Lin, Kun; Lu, Shun; He, Xiao-Ming; He, Wei; Wei, Qiu-Shi; Xiang, Xiao-Wei; He, Min-Cong (Frontiers in Cell and Developmental Biology, 2023)
Background: Steroid-induced Osteonecrosis of the Femoral Head (SIONFH) is a skeletal disease with a high incidence and a poor prognosis. Whole-body vibration therapy (WBVT), a new type of physical training, is known to promote bone formation. However, it remains unclear whether WBVT has a therapeutic effect on SIONFH. Materials and methods: Thirty adult male and female Sprague-Dawley (SD) rats were selected and randomly assigned to three experimental groups: the control group, the model group, and the mechanical vibration group, respectively. SIONFH induction was achieved through the combined administration of lipopolysaccharides (LPS) and methylprednisolone sodium succinate for injection (MPS). The femoral head samples underwent hematoxylin and eosin (H&E) staining to visualize tissue structures. Structural parameters of the region of interest (ROI) were compared using Micro-CT analysis. Immunohistochemistry was employed to assess the expression levels of Piezo1, BMP2, RUNX2, HIF-1, VEGF, CD31, while immunofluorescence was used to examine CD31 and Emcn expression levels. Results: The H&E staining results revealed a notable improvement in the ratio of empty lacuna in various groups following WBVT intervention. Immunohistochemical analysis showed that the expression levels of Piezo1, BMP2, RUNX2, HIF-1, VEGF, and CD31 in the WBVT group exhibited significant differences when compared to the Model group (P＜0.05). Additionally, immunofluorescence analysis demonstrated statistically significant differences in CD31 and Emcn expression levels between the WBVT group and the Model group (P＜0.05). Conclusion: WBVT up-regulates Piezo1 to promote osteogenic differentiation, potentially by enhancing the HIF-1α/VEGF axis and regulating H-vessel angiogenesis through the activation of the Piezo1 ion channel. This mechanism may lead to improved blood flow supply and enhanced osteogenic differentiation within the femoral head.